2014
DOI: 10.3171/2013.11.spine13392
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional motion analysis of the cervical spine for comparison of anterior cervical decompression and fusion versus artificial disc replacement in 17 patients

Abstract: Object Cervical arthroplasty with an artificial disc (AD) has emerged as an alternative to anterior cervical discectomy and fusion (ACDF) for the management of cervical spondylosis. This study aims to provide 3D motion analysis data comparing patients after ACDF and AD replacement. Methods Ten patients who underwent C5–6 ACDF and 7 who underwent C5–6 AD replacement were enrolled. Using biplanar fluoroscopy and a model-based track technique (accurate up to 0.6 mm and 0.6°), motion analysis of axial rotation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…In agreement with ROM and ICR results, it does not appear that single‐level cervical arthrodesis affects the pattern of cervical motion segment contributions to flexion/extension . Studies that report that adjacent segment contributions are increased after arthrodesis in comparison to after arthroplasty must be interpreted carefully . Due to the arthrodesis, motion will be lost at the operated motion segment, reducing the total cervical spine ROM.…”
Section: Cervical Spine Kinematicssupporting
confidence: 53%
See 2 more Smart Citations
“…In agreement with ROM and ICR results, it does not appear that single‐level cervical arthrodesis affects the pattern of cervical motion segment contributions to flexion/extension . Studies that report that adjacent segment contributions are increased after arthrodesis in comparison to after arthroplasty must be interpreted carefully . Due to the arthrodesis, motion will be lost at the operated motion segment, reducing the total cervical spine ROM.…”
Section: Cervical Spine Kinematicssupporting
confidence: 53%
“…These limitations were initially addressed individually, by using MRI images to track three‐dimensional spine kinematics in static supine positions, and by using single‐plane fluoroscopic imaging in combination with computer software to automatically track two‐dimensional dynamic vertebral body movement . More recently, imaging systems have been developed to collect synchronized biplane radiographs during functional three‐dimensional movements . Several groups have demonstrated that vertebral motion can be tracked with an accuracy of better than 1 mm and one degree during dynamic multi‐planar movements using this technology .…”
Section: Advances In Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…McDonald et al reported that there may be some degree of hypermobility at non-operative segments subsequent to an ACDF procedure, which has been suggested to result in increased compressive axial stress between the articulating surfaces, thereby facilitating cartilage degeneration [15]. According to Kim et al the postoperative ROM might even be underestimated because it might temporarily decrease due to persisting axial neck pain during the early postoperative period [16].…”
Section: Discussionmentioning
confidence: 98%
“…A great variety of biomechanical studies have been published about cervical arthroplasty. Most studies focus on the ROM or on changes in disc height and facet translation compared with normal individuals and with patients after ACDF, or on clinical results [9][10][11][12][13][14][15][16][17][18][19][20][21]. Several studies also investigate qualitative motion of disc prostheses [1][2][3][4][5][6][7][8]22], but we did not nd studies investigating how the COR after insertion of a prosthesis compares with healthy individuals, which is important because our data shows that the COR in patients with disc herniations is not at a physiological position anymore and therefore the prae-op COR cannot be used as reference:…”
Section: Discussionmentioning
confidence: 99%